Insights into Collaborative Research on Emerging Media Impact on Consumer Behavior: Wawasan tentang Penelitian Kolaboratif tentang Dampak Media yang Sedang Berkembang terhadap Perilaku Konsumen - Amalia , Fara Putri; Puspitasari, Puspitasari; Saputra , Muhammad Rizky; Abadi , Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study conducts a bibliometric analysis from 2010 to 2023 using Crossref data to explore trends in research on mass media and social media's impact on consumer behavior. Analysis using VOSviewer software reveals